Pengaruh Tenaga Kerja dan IPM Terhadap Pertumbuhan PDB Industri Manufaktur di Indonesia - Nisa Ul Fitria; Sri Wahyuni; Asrida Asrida (LPPM Institut Pendidikan Nusantara Global, 2026)
The manufacturing industry has been considered the main driver of structural transformation in Indonesia, and economic growth is a key indicator of national development. Although the manufacturing industry contributes significantly to the national gross domestic product (GDP), there are a number of structural obstacles that hinder its growth. The most prominent of these are the mismatch between education and employment and the level of labor. The sustainability and competitiveness of the manufacturing industry are questionable due to its dependence on the quality of human resources. Therefore, this study analyzes the influence of labor and the Human Development Index (HDI) on the GDP of the manufacturing industry in Indonesia. This study uses a quantitative approach with time series data from 1995 to 2024. The method used is Autoregressive Distributed Lag (ARDL) to test long-term and short-term cointegration to capture imbalances towards the long term using Eviews 13. The results of this study indicate that the manufacturing industry workforce significantly affects manufacturing industry GDP growth in the long and short term, while HDI does not significantly affect manufacturing industry GDP growth in the long and short term. The error correction coefficient is negative and statistically significant at -0.619, indicating that approximately 61.9% of the short-term imbalance in the previous period is corrected in the current period of long-term equilibrium. This shows that industrial output is more responsive to production capacity (labor) than to aggregate human quality. Policy implications are more directed at optimizing industrial labor absorption in supporting manufacturing sector growth.